2008
DOI: 10.1186/1749-8104-3-35
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube derived Wnt signals cooperate with FGF signaling in the formation and differentiation of the trigeminal placodes

Abstract: Background: Neurogenic placodes are focal thickenings of the embryonic ectoderm that form in the vertebrate head. It is within these structures that the precursors of the majority of the sensory neurons of the cranial ganglia are specified. The trigeminal placodes, the ophthalmic and maxillomandibular, form close to the midbrain-hindbrain boundary and many lines of evidence have shown that signals emanating from this level of the neuraxis are important for the development of the ophthalmic placode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 31 publications
3
63
0
Order By: Relevance
“…This area will give rise to the otic, lateral line, and epibranchial placodes, with otic placodes being favored by Wnt and epibranchial placodes by persistent FGF signaling (Freter, Muta, Mak, Rinkwitz, & Ladher, 2008;Ladher, Anakwe, Gurney, Schoenwolf, & Francis-West, 2000;Nechiporuk, Linbo, Poss, & Raible, 2007;Ohyama, Mohamed, Taketo, Dufort, & Groves, 2006). The profundal placode marked by Pax3 expression and the trigeminal placode are induced in between by various signals (Wnt, FGF, PDGF) from the neural plate (Canning, Lee, Luo, Graham, & Jones, 2008;Lassiter et al, 2007;McCabe & Bronner-Fraser, 2008). …”
Section: Origin and Patterning Of Cranial Placodesmentioning
confidence: 97%
“…This area will give rise to the otic, lateral line, and epibranchial placodes, with otic placodes being favored by Wnt and epibranchial placodes by persistent FGF signaling (Freter, Muta, Mak, Rinkwitz, & Ladher, 2008;Ladher, Anakwe, Gurney, Schoenwolf, & Francis-West, 2000;Nechiporuk, Linbo, Poss, & Raible, 2007;Ohyama, Mohamed, Taketo, Dufort, & Groves, 2006). The profundal placode marked by Pax3 expression and the trigeminal placode are induced in between by various signals (Wnt, FGF, PDGF) from the neural plate (Canning, Lee, Luo, Graham, & Jones, 2008;Lassiter et al, 2007;McCabe & Bronner-Fraser, 2008). …”
Section: Origin and Patterning Of Cranial Placodesmentioning
confidence: 97%
“…FGF and Wnt signaling pathways cross talk, in either cooperative or antagonistic fashions, in several developmental and cellular processes, such as embryonic morphogenesis and patterning, cell proliferation, cell fate determination and tissue induction (Gunhaga et al, 2003;Katoh, 2006;Takemoto et al, 2006;Canning et al, 2008;Hong et al, 2008). Cross-interaction between these pathways can further modulate individual fluctuations of each signal, generating specific intracellular environments in different tissues and/or developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…At the midbrain level of stage nine embryos, Pax3 protein expression was first observed in the dorsal part of the midbrain-level PPR (not shown), and at later stages such as stage 11, this expression expanded ventro-laterally (Fig. 2) as previously described by Canning et al 2008 at the mRNA level. Six1 expression confirmed the placodal identity of this Pax3-domain (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Previous studies indicated that platelet-derived growth factor and Wnt ligands provided by the midbrain and midbrain ⁄ hindbrain boundary region induce Pax3 expression expanding from a medial to ventro-lateral direction (Lassiter et al 2007;Canning et al 2008;McCabe & Bronner-Fraser 2008). Pax3 function is important for the promotion of further differentiation of trigeminal placode ⁄ sensory neurons (Dude et al 2009).…”
Section: Introductionmentioning
confidence: 99%